Galaxy formation in the Santa Cruz semi-analytic model compared with IllustrisTNG – I. Galaxy scaling relations, dispersions, and residuals at z = 0. Issue 4 (23rd August 2022) - Gabrielpillai, Austen; Somerville, Rachel S; Genel, Shy; Rodriguez-Gomez, Vicente; Pandya, Viraj; Yung, L Y Aaron; Hernquist, Lars
ABSTRACT: We present the first results from applying the Santa Cruz semi-analytic model (SAM) for galaxy formation on merger trees extracted from a dark matter only version of the IllustrisTNG (TNG) simulations. We carry out a statistical comparison between the predictions of the Santa Cruz SAM and TNG for a subset of central galaxy properties at z = 0 with a focus on stellar mass, cold and hot gas mass, star formation rate (SFR), and black hole (BH) mass. We find fairly good agreement between the mean predictions of the two methods for stellar mass functions and the stellar mass versus halo mass (SMHM) relation, and qualitatively good agreement between the SFR or cold gas mass versus stellar mass relation and quenched fraction as a function of stellar mass There are greater differences between the predictions for hot (circumgalactic) gas mass and BH mass as a function of halo mass. Going beyond the mean relations, we also compare the dispersion in the predicted scaling relations, and the correlation in residuals on a halo-by-halo basis between halo mass and galaxy property scaling relations. Intriguingly, we find similar correlations between residuals in SMHM in the SAM and in TNG, suggesting that these relations may be shaped by similar physical processes. Other scaling relations do not show significant correlations in the residuals, indicating that the physics implementations in the SAM and TNG are significantly different.